Dispersion of Islamic Preaching: some Quranic Viewpoints on the Idea of Tourism - Abur Hamdi Usman; Mohd Farid Ravi Abdullah; Syarul Azman Shaharuddin; Azwar Iskandar (Universitas Ahmad Dahlan, 2022)
The spread of Islamic preaching and all efforts towards this direction should be done in their entirety because this represents the nature of Islam itself. As a result, Islamic preaching should be a part of everyday life as a human being, which is not limited to a person's lifestyle. Islamic preaching requires a great deal of man's power of quality and quantity, excellent in spiritual strength, open-mindedness and professionalism. This article seeks to analyze the factors of how the Islamic preaching spread across the globe while making tourism one of the most common mediums for preaching. Using a descriptive qualitative approach and evidence of history, this article reveals the impact of Islamic tourism on the spread of religion on a global scale, as it is crucial to take this result seriously and pay close attention to making Islam the centre of attraction.